LAUGHTER YOGA SEBAGAI PENDEKATAN KOMPLEMENTER UNTUK PERBAIKAN DIMENSI REGULASI EMOSI PADA PASIEN KANKER - Yesiana Dwi Wahyu Werdani; Arief Widya Prasetya (JPK : Jurnal Penelitian Kesehatan, 2026)
Abstract: Cancer patients have difficulty controlling emotions because of their illness. One of the complementary therapy was laughter yoga. This study aimed to examine the effect of laughter yoga in improving two dimensions of emotion regulation in cancer patients. Method used a quasi-experimental design with a non-equivalent control group. Population all of cancer patients in Indonesian Cancer Foundation Each Java Branch. 40 participants taken by purposive sampling based on inclusion criteria. Samples consist of 20 participants as an intervention group were given the laughter yoga 8x for a month. Meanwhile 20 participants as the control group received routine therapy as usual. Instrument used the Emotion Regulation Questionnaire (ERQ) consist of reappraisal and suppression dimensions. The statistical test used paired t-test and independent t-test. Result showed in experimental group, reappraisal increased from 19.7 + 2.43 to 34.6 + 1.95 (p = 0.007) and suppression decreased from 19.5 + 2.43 to 15.8 + 2.04 (p = 0.000). While the control group reappraisal slightly increased from 19.1 + 1.58 to 27.9 + 2.15 (p = 0.000) and suppression stagnation from 19.0 + 1.58 to 19.2 + 1.64 (p = 0.104). The hypothesis test conducted between the two groups by independent test p value 0.000. Laughter yoga effectively improved emotion regulation in the reappraisal and suppression dimensions among cancer patients. Regular practice of laughter yoga as a complementary therapy approach for cancer patients improve the emotion regulation, because the laughter yoga process facilitates positive cognitive reappraisal and promotes adaptive interpretation of diverse emotional experiences.